SMART CITY DI KOTA BANDUNG: SUATU TINJAUAN ASPEK TEKNOLOGI, MANUSIA, DAN KELEMBAGAAN - Eko Budi Santoso; Annisa Rahmadanita (Jurnal Teknologi dan Komunikasi Pemerintahan, 2020)
This article is the result of a research which aims to describe the implementation of Smart city in Bandung in terms of technology, human and institutional aspects. The research was conducted with a descriptive qualitative approach. Data collection was carried out by semi-structured interviews with 37 informants, observation and documentation. The research findings show that the socialization related to the smart city program, especially in socializing service applications to the public, is still not widespread so that it has an impact on the lack of citizen knowledge regarding the smart city program and the Bandung City Government has ratified the Bandung Smart city master plan standard operating procedures related to information systems in order to realize smart city ​​in the city of Bandung. It is recommended to increase continuous socialization, educate the public regarding online applications in collaboration with campuses, as well as implement the Bandung Smart City master plan and conduct evaluations at each stage that has been implemented. Keywords: Smart city, Technology, Human, Institutional, Bandung City